MATLAB/Simulink of a Solar Photovoltaic System through Cuk Converter (International Journal of Engineering and Computer Science, 2016)
In parallel to developing technology, demand for more energy makes us seek new energy sources. The most important application field of this research is renewable energy resources. Solar energy is being popular ones owing to abundant, ease of availability and convertibility to the electric energy. This paper covers a detailed analysis of solar PV system with Cuk converter such that it gives constant and stepped up dc voltage to the load. A Cuk Converter is used for examine the performance of solar PV system. Simulink of cuk converter in PV system and analyzing output voltage through MATLAB